Empowering Primiparous Mothers Through Kegel Exercise: A Strategy to Enhance Sexual Self Efficacy During the Post Partum Period - Tina Mawardika; Umi Aniroh (Indonesian Journal of Global Health Research, 2025)
The postpartum period is a critical phase marked by significant physical and psychological changes, particularly for primiparous mothers who are experiencing childbirth for the first time. One of the common challenges encountered during this period is a decrease in sexual self-efficacy, defined as the individual's confidence in engaging in a healthy and satisfying sexual life. This study aimed to examine the effect of Kegel exercise education on improving sexual self-efficacy among primiparous women. A quasi-experimental design with a pretest-posttest control group approach was employed. The intervention consisted of structured Kegel education delivered through sequential stages: situational analysis, problem identification, planning, and implementation. The study sample consisted of 34 primiparous mothers from the Lerep Public Health Center working area, divided equally into intervention and control groups using purposive sampling. Respondents in the intervention group were those who received Kegel exercise education, while the control group consisted of those who did not receive any intervention. Univariate analysis was conducted using central tendency, while bivariate analysis was performed using the Man Whitney, which showed a p-value of 0.01 < α (0.05). The results demonstrated a statistically significant improvement in the sexual self-efficacy of the intervention group compared to the control group. It can be concluded that Kegel exercise education is an effective and empowering strategy to support the recovery of sexual function and improve the quality of life in primiparous women during the postpartum period.